Testing cost-effective methodologies for flood and seismic vulnerability assessment in communities of developing countries (Dajç, northern Albania). Issue 3 (3rd May 2016) - Pazzi, Veronica; Morelli, Stefano; Fidolini, Francesco; Krymi, Elvis; Casagli, Nicola; Fanti, Riccardo
Abstract : Nowadays many developing countries need effective measures to reduce the disaster related risks. Structural interventions are the most effective to achieve these aims. Nevertheless, in the absence of adequate financial resources different low-cost strategies can be used to minimize losses. The purpose of this paper is to demonstrate that the disaster risk reduction can be gathered building a community coping capacity. In the case study, flood and seismic analyses have been carried out using relatively simple and low-cost technologies, fundamental for governments and research institutions of poorly developed countries. In fact, through the acquisition and dissemination of these basic information, a reduction of vulnerability and risk can be achieved. In detail, two methodologies for the evaluation of hydraulic and seismic vulnerability were tested in the Dajç municipality (Northern Albania), a high-seismicity region that is also severely affected by floods. Updated bathymetric, topographic and hydraulic data were processed with HEC-RAS software to identify sites potentially affected by dykes overflowing. Besides, the soil-structure interaction effects for three strategic buildings were studied using microtremors and the Horizontal to Vertical Spectral Ratio method. This flood and seismic vulnerability analysis was then evaluated in terms of costs and ease of accessibility in order to suggest the best use both of the employed devices and the obtained information for designing good civil protection plans and to inform the population about the right behaviour in case of threat.